Faeröerne i 1:100 000 / Geodetisk Instituts Topografiske Kort (Geodetisk Instituts, 1932)
Relief shown by contours, hachures and spot heights. Depths shown by soundings.; Shows Copenhagen and Greenwich meridians. Color; 1:100,000